The origins of neoliberalism : modeling the economy from Jesus to Foucault - Leshem, Dotan (Columbia University Press, 2016)
Dotan Leshem recasts the history of the West from an economic perspective, bringing politics, philosophy, and economics closer together and revealing the significant role of Christian theology in shaping economic and political thought. He begins with early Christianity engagement with economic knowledge and the influence of this interaction on politics and philosophy. He then follows the secularization of economics in liberal and neoliberal theory, showing it to be a perversion of earlier communitarian tradition. Only by radically relocating the origins of modernity in late antiquity, Leshem argues, can we confront neoliberalism.